The Effect of STEAM-based Learning on Students’ Concept Mastery and Creativity in Learning Light And Optics - Gita Ayu Wandari; Agus Fany Chandra Wijaya; Rika Rafikah Agustin (Journal of Science Learning, 2018)
The integrated knowledge should be implemented to face the 21st-century era. Beside the integrated knowledge, mastery the concept and creativity also must be involved in order to enhance the quality of education. Thus, this research was aimed to investigate the effect of STEAM-Based Learning on Students’ Concept Mastery and Creativity in learning Light and Optics. The method that used was a mixed method with convergent parallel design. The population in this research was 8th-grade students in private junior high school in West Bandung and the sample was one class of 8th grade. The school implemented Indonesian Curriculum 2013 in the teaching-learning process. The sampling techniques were convenience sampling. The number of participants in this research was 27 students. The quantitative data in this research was obtained through an objective test. The objective test was made based on Bloom’s Taxonomy revision by Anderson. The qualitative data was obtained through the creativity rubric adopted from Creative Product Semantic Scale (CPSS) developed by O’Quinn and Bessemer. The dimension that was in creativity is novelty, resolution, and elaboration and synthesis. According to the research, students’ concept mastery improved as much as 0.78 with category high improvement after the implementation of STEAM-Based Learning. For students’ creativity achievement, in every dimension gained different result: 1) Novelty is categorized into good with 75.6%, 2) Resolution is categorized into good with 77.8%, and 3) Elaboration and synthesis are categorized into enough with 65.3 %. Overall, students’ concept mastery and creativity in the implementation of STEAM-Based Learning in learning light and optic is categorized as good.